Peningkatan Imunitas dan Kualitas Hidup Lansia Melalui Penerapan Program Pola Hidup Sehat dengan Pemanfaatan Bahan Pangan Lokal, Desa Badean, Banyuwangi - Al Amin, Muhammad; Najib, Ainun; Rajab, Alfian Abdul; Amanda, Efina (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This community service program aims to enhance the immunity and quality of life of the elderly in Badean Village, Banyuwangi, through the implementation of healthy lifestyle practices utilizing local food ingredients. The program's background is rooted in the increasing elderly population, who tend to experience a decline in immunity (immunosenescence) and quality of life, necessitating comprehensive health interventions. The methodology employed is a community-based participatory approach, actively involving the elderly, their families, health cadres, and community leaders. Key program activities include balanced nutrition education, practical training on processing local food ingredients, promotion of adaptive physical activities, and capacity building for health cadres as health facilitators. The program results demonstrate a significant positive impact. There was an increase in the elderly's knowledge about healthy lifestyles and nutrition from 55% to 73%. Behavioral observations indicated an increase in the consumption of local vegetables and fruits (70%) and regular participation in physical activities (60%). The utilization of local food ingredients for daily diets also notably increased. Qualitatively, the elderly reported an improvement in their physical (more energetic) and psychological (happier) quality of life, as well as a decrease in the frequency of minor health complaints. This program successfully demonstrated that community-based interventions optimizing local food resources are an effective and sustainable strategy for improving the health and well-being of the elderly, while simultaneously empowering the community.